Molecular cloning and physical characterization of a chromosomal hemolysin from Escherichia coli. - Welch, R A (1983)
A chromosomal hemolysin determinant was isolated in the form of recombinant plasmid pSF4000 from a human urinary tract isolate. Escherichia coli J96. A restriction endonuclease fragment map of pSF4000 was constructed. The ampicilin resistance transposon Tn/ was used as a site-specific mutagen in conjunction with in vitro derived deletions to localize the hemolysin determinant to a 7.0-kilobase region of pSF4000. Seventeen hemolytic E. coli isolates from human urinary tract infections were found to share similar DNA sequences with J96 hemolysin sequences, using a hemolysin-specific restriction endonuclease fragment as a hybridization probe. In all 17 hemolytic E. coli strains the hemolysin gene sequences were localized to the bacterial chromosome. The hemolysin-specific gene sequences can be found only in hemolytic strains by colony blot hybridization, suggesting that in the evolutionary sense the hemolysin-specific genetic sequences have only recently been introduced into the E. coli chromosome. Evidence is also presented that in the regions neighboring the J96 chromosomal hemolysin there are additional unique DNA sequences not commonly found in other E. coli isolates.